VITAMIN D STATUS IN THALASSEMIA MAJOR: AN UPDATE - Ashraf Tawfik Soliman (Mediterranean Journal of Hematology and Infectious Diseases)
The survival of patients with thalassemia major has progressively improved with advances in therapy; however, osteoporosis and cardiac dysfunction remain frequent complications. Adequate circulating levels of vitamin D are essential for optimal skeletal health and reducing fracture risk. Vitamin D deficiency and insufficiency is reported to be high in thalassemic patients in many countries despite the presence of good sunshine and routine prescription of 400–1,000 IU vitamin D per day. The risk of vitamin D deficiency in thalassemia and its relation to bone disease; including osteoporosis, rickets, scoliosis, spinal deformities and fractures as well as to cardiac dysfunction is discussed in this mini-review. Monitoring and maintaining normal serum level of 25-OH vitamin D through oral intake of vitamin D and early correction of VDD by oral or parental use of vitamin D may significantly improve bone mineral accretion and ameliorate cardiac function. The survival of patients with thalassemia major has progressively improved with advances in therapy; however, osteoporosis and cardiac dysfunction remain frequent complications. Adequate circulating levels of vitamin D are essential for optimal skeletal health and reducing fracture risk. Vitamin D deficiency and insufficiency is reported to be high in thalassemic patients in many countries despite the presence of good sunshine and routine prescription of 400–1,000 IU vitamin D per day. The risk of vitamin D deficiency in thalassemia and its relation to bone disease; including osteoporosis, rickets, scoliosis, spinal deformities and fractures as well as to cardiac dysfunction is discussed in this mini-review. Monitoring and maintaining normal serum level of 25-OH vitamin D through oral intake of vitamin D and early correction of VDD by oral or parental use of vitamin D may significantly improve bone mineral accretion and ameliorate cardiac function.